PENERAPAN PEMBELAJARAN KOOPERATIF MODEL JIGSAW LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII.6 SMP NEGERI 18 PEKANBARU PADA MATERI FUNGSI TAHUN PELAJARAN 2017/2018 - MARDIAH, TENGKU (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2018)
Abstract This study aims to determine the effort to improve students' Mathematics in the form of Fungsi through Jigsaw Learning model in class VIII.6 in SMP Negeri 18 Pekanbaru. This form of research is a classroom action research with as many as two rounds (Cycle). Each round is done with four stages of planning, implementation, observation and reflection. The subjects of this study are the students of class VIII.6 in SMP Negeri 18 Pekanbaru with a total of 38 students consisting of 21 male students and 17 female students. The data obtained in the form of English learning result obtained from the test and observation sheet of teaching and learning activities. Data collection methods used include test, observation and documentation. From the results in the first cycle of student learning outcomes to 40% with inactive classification. While in cycle II result of student in learning experience increase to become 60% with very active classification. This situation shows that improvements in Mathematics learning process with Jigsaw Learning model in Mathematics subjects in grade VIII.6 students at SMP Negeri 18 Pekanbaru can be said to be fully successful. Keywords : Learning Outcomes, Mathematics, Fungsi, Jigsaw Learning